2018
DOI: 10.1002/ange.201807185
|View full text |Cite
|
Sign up to set email alerts
|

Global Aromaticity in Macrocyclic Cyclopenta‐Fused Tetraphenanthrenylene Tetraradicaloid and Its Charged Species

Abstract: As table cyclopenta-fused tetraphenanthrenylene macrocycle, CPTP-M,w as synthesized, and the structure was confirmed by X-rayc rystallographic analysis.I te xhibits al arge radical character (number of unpaired electron, N U = 3.52) and asmall singlet-triplet energy gap (DE S-T = À2.8 kcal mol À1 by SQUID). Its backbone contains 60 ([4n]) conjugated p electrons and is globally antiaromatic.N MR measurements and theoretical calculations revealed that its dication/dianion is globally aromatic owing to the existe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 39 publications
4
7
0
Order By: Relevance
“…While our work was close to completion, 22 Wu et al reported their concurrent research on 3a, based on an essentially identical synthetic strategy. 23 The present account is therefore focused on the anion-binding capability of 3a and its relationship to the redox chemistry of this open-shell coronoid. DFT optimization of the singlet state, is shown in Figure 1.…”
Section: ■ Introductionsupporting
confidence: 67%
“…While our work was close to completion, 22 Wu et al reported their concurrent research on 3a, based on an essentially identical synthetic strategy. 23 The present account is therefore focused on the anion-binding capability of 3a and its relationship to the redox chemistry of this open-shell coronoid. DFT optimization of the singlet state, is shown in Figure 1.…”
Section: ■ Introductionsupporting
confidence: 67%
“…It has been reported that for rings consisting of localized single and double bonds, very small and negative HOMA values are obtained, suggesting its nonaromatic nature. 38,39 Thus, the spectral and electrochemical properties predicted by DFT agreed closely with the experimental data. In short, the absence of bond length equalization, low-field 1 H NMR shifts, small NICS values, and nonplanar structure 40 undoubtedly supports the nonaromatic nature of macrocycle 4.…”
Section: ■ Results and Discussionsupporting
confidence: 74%
“…For the quantitative evaluation of aromaticity, the NICS and harmonic oscillator model of aromaticity (HOMA) values were calculated for macrocycle 4 . The isotropic NICS (NICS(0) iso ) and the zz component of the shielding tensor (NICS(0) zz ) values in the S 0 state for the compound 4 are −0.6220 and +4.5369, respectively, suggesting its nonaromatic nature. Thus, the molecule lacks both local and ground-state global aromaticity. The HOMA indices were calculated along various π-conjugation paths using the optimized structure for macrocycle 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, one additional double-bond has been broken to have diradical (2 unpaired electrons) to tetraradical (4 unpaired electrons) and reaching up to hexadecaradical (16 unpaired electrons) characters (Figures S29-S32). Although the polyradical characters are comparable with the reported values in the literature (Das et al, 2016;Lu et al, 2018;Liu et al, 2019), to date, radical characters beyond decaradical is not reported for macrocycles. Owing to the symmetric structure of all the macrocycles, higher energy orbitals are found to be degenerate (Figures S33--S35).…”
Section: Evolution and Origins Of Polyradical Character (Y I )supporting
confidence: 87%